2011
DOI: 10.1111/j.1365-2710.2011.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Indirect comparison of biological treatments in refractory rheumatoid arthritis

Abstract: The biological drugs used in rheumatoid arthritis are no different in efficacy. Their therapeutic positioning depends on their relative safety and convenience profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
0
19
0
6
Order By: Relevance
“…The effectiveness of TCZ is comparable to that of each of the TNF inhibitors with respect to ACR20 and ACR50 responses, but greater than that of the TNF inhibitors with respect to ACR70 response. Another systematic review of selected clinical trials involving combination therapy with MTX concluded that there was no difference in efficacy on the basis of ACR50 response criterion at 24/30 weeks between TNF inhibitors and TCZ 25. Turkstra et al reported a mixed treatment comparison of the short-term efficacy of nine bDMARDs, including TNF inhibitors and TCZ in patients with established RA 26.…”
Section: Comparative Efficacy Studies Of Tcz Ada and Other Tnf Inhimentioning
confidence: 99%
“…The effectiveness of TCZ is comparable to that of each of the TNF inhibitors with respect to ACR20 and ACR50 responses, but greater than that of the TNF inhibitors with respect to ACR70 response. Another systematic review of selected clinical trials involving combination therapy with MTX concluded that there was no difference in efficacy on the basis of ACR50 response criterion at 24/30 weeks between TNF inhibitors and TCZ 25. Turkstra et al reported a mixed treatment comparison of the short-term efficacy of nine bDMARDs, including TNF inhibitors and TCZ in patients with established RA 26.…”
Section: Comparative Efficacy Studies Of Tcz Ada and Other Tnf Inhimentioning
confidence: 99%
“…Recently biological agents (biologics), especially tumor necrosis factor antagonists (anti-TNFs, TNF-i), have demonstrated considerable efficacy in treating patients with RA who do not respond or show intolerance to traditional DMARDs [1-3]. Many randomized controlled trials (RCTs) comparing their efficacy with placebo treatment in DMARD-refractory patients have been published, as well as systematic reviews (SRs) and overviews of SRs of these RCTs [4].…”
Section: Introductionmentioning
confidence: 99%
“…Изучены Национальные рекомендации по лечению РА [4], в которых дается заключение об отсутст-вии значимого различия в эффективности [1][2][3] и то-ксичности [26][27][28][29] различных ГИБП. Сообщается, что у па-циентов с РА, резистентных к стандартным БПВП, препара-тами выбора являются ингибиторы фактора некроза опухо-ли (ФНО) α, однако в качестве первого ГИБП возможно на-значение абатацепта (АБЦ), ритуксимаба (РТМ) и тоцили-зумаба (ТЦЗ), которые, согласно результатам систематиче-ских обзоров, не отличаются по эффективности и безопас-ности от ингибиторов ФНОα (уровень доказательности А) [2,3,[5][6][7][8][16][17][18][19][20][21][22][23][24][25]. Аналогичные выводы о равной эффектив-ности ГИБП, применяемых в лечении РА у пациентов, рези-стентных к терапии метотрексатом (МТ) и другими БПВП [29,30], сделаны отечественными авторами [31].…”
unclassified
“…[22], посвящен-ном эффективности различных ГИБП у больных РА, для не-прямого сравнения эффективности этих препаратов отобраны 10 рандомизированных плацебоконтролируемых исследова-ний, демонстрирующих частоту ответа по критериям Амери-канской коллегии ревматологов (ACR) к 24-30-й неделе лече-ния. Авторами сделано заключение об отсутствии различий в эффективности ГИБП, применяемых для лечения РА.…”
unclassified
See 1 more Smart Citation